1996
DOI: 10.1097/00007890-199612270-00008
|View full text |Cite
|
Sign up to set email alerts
|

Apyrase Administration Prolongs Discordant Xenograft Survival1,2,3,4

Abstract: Platelet thrombi and vascular inflammation are prominent features of discordant xenograft rejection. The purinergic nucleotides ATP and ADP, which are secreted from platelets and released by injured endothelial cells (EC), are important mediators of these reactions. Quiescent EC express the ectoenzyme ATP-diphosphohydrolase (ATPDase; an apyrase), which exerts an important thromboregulatory function by hydrolyzing both ATP and ADP. We have shown that ATPDase activity is rapidly lost from the surface of the EC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 18 publications
3
55
0
Order By: Relevance
“…We speculate that this loss, and the resultant decreased capacity to degrade ADP, could play a significant role in the extensive platelet activation and vascular inflammation seen in graft rejection and other forms of vascular injury. Certainly, the intravenous administration of apyrases to experimental animals has been shown to prolong xenograft survival and abrogate the platelet activation and deposition seen in this setting (26).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this loss, and the resultant decreased capacity to degrade ADP, could play a significant role in the extensive platelet activation and vascular inflammation seen in graft rejection and other forms of vascular injury. Certainly, the intravenous administration of apyrases to experimental animals has been shown to prolong xenograft survival and abrogate the platelet activation and deposition seen in this setting (26).…”
Section: Discussionmentioning
confidence: 99%
“…Although ecto-ATPases are active in the presence of both Ca 2 ϩ and Mg 2 ϩ , they might have some ion-dependent "territorial dominance" on the EC surface in addition to their different sensitivity for pH and stress by injury or inflammation. Recently, several studies have appeared on the loss of ecto-ATPase activity on vascular ECs after injury or oxidative stress (Candinas et al 1996;Koyamada et al 1996;Robson et al 1997;Gayle et al 1998). The loss of ecto-ATPase activity may result in platelet aggregation, thrombosis, and xenograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Because CD39 destroys extracellular ATP and ADP, ADP concentrations would therefore be expected to rise, favoring clotting [102]. It has therefore been suggested that externally administered apyrase might be a useful antithrombotic agent [103].…”
Section: Biological Properties Of the E-ntpdase Familymentioning
confidence: 99%